2017
DOI: 10.1115/1.4037909
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Performance of a Transonic Turbine Blade Passage in the Presence of Leakage Flow Through Upstream Slot and Mateface Gap With Endwall Contouring

Abstract: Comparison of heat transfer performance of a nonaxisymmetric contoured endwall to a planar baseline endwall in the presence of leakage flow through stator–rotor rim seal interface and mateface gap is reported in this paper. Heat transfer experiments were performed on a high turning turbine airfoil passage at Virginia Tech's transonic blow down cascade facility under design conditions for two leakage flow configurations—(1) mateface blowing only, (2) simultaneous coolant injection from the upstream slot and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…(Thrift et al, 2012) showed that a slot angle of 45°increases cooling effectiveness (compared to 90°) due to a different formation of the horseshoe vortex. An overall averaged reduction in Nusselt number for the endwall, both with and without purge flow, was reported by (Roy et al, 2017) for a contoured endwall due to secondary flow control. Further, (Lynch et al, 2010) reported a 3.1% reduction of averaged heat transfer for endwall contouring.…”
Section: Introductionmentioning
confidence: 85%
“…(Thrift et al, 2012) showed that a slot angle of 45°increases cooling effectiveness (compared to 90°) due to a different formation of the horseshoe vortex. An overall averaged reduction in Nusselt number for the endwall, both with and without purge flow, was reported by (Roy et al, 2017) for a contoured endwall due to secondary flow control. Further, (Lynch et al, 2010) reported a 3.1% reduction of averaged heat transfer for endwall contouring.…”
Section: Introductionmentioning
confidence: 85%
“…It is important to understand where the models provide reasonable estimates of Nu, since that information is important to a designer considering cooling schemes for the endwall. Both Lynch and Thole [19] and Roy et al [21] indicate that gap leakage increases local heat transfer coefficients relative to no flow, but also provides significant cool air to the aft suction side region and generally results in lower heat flux.…”
Section: Effect Of Midpassage Gap Leakage For Aligned Endwallsmentioning
confidence: 99%
“…Although this ejected fluid can locally increase heat transfer significantly (>200% relative to the upstream endwall), it is also a source of cooling air. A series of studies with realistic endwall conditions and endwall contouring in a transonic facility by Jain et al [20] and Roy et al [21] also concluded that a majority of the gap leakage flow was located near the throat, and that a contoured endwall improved coolant distribution relative to a flat endwall.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…(Thrift et al, 2012) showed that a slot angle of 45 deg increases cooling effectiveness compared to 90 deg due to a different formation of the horse shoe vortex. An overall averaged reduction in Nusselt number for the endwall with and without purge flow is reported by (Roy et al, 2017) for a contoured endwall due to secondary flow control. Also (Lynch et al, 2010) reported a reduction by 3.1% of averaged heat transfer for endwall contouring.…”
Section: Introductionmentioning
confidence: 98%